PENGARUH IKLIM ORGANIASI DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PT. CHAROEN POKPHAND INDONESIA MEDAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVINING - Ritonga, Sinar (Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study is to determine the influence of organizational climate and work ethic on employee performance at PT. Charoen Pokphand Indonesia Medan with motivation as an intervining variable. The population in this study were all company employees as many as 62 people. Taking into account the relatively small number of members of the population, all members of the population are the object of research. The types and sources of data used in this study are primary data are data obtained through interviews, and through the distribution of questionnaires to responde, secondary data is data obtained through document collection using the documentation method. The analysis technique used is multiple linear regression analysis. The results showed that work climate and work ethic partially and simulutanly had a significant effect on work motivation and work climate, work ethic and work motivation partially and significantly had a positive and significant effect on employee performance.